Nasolabial cyst in an unusual location within the upper lip – A rare case report - Sushruth Nayak; Prachi Nayak; Kush Pathak; Surbhi Singh; Asha Karadwal (Advances in Human Biology, 2022)
The nasolabial cyst is a rare non-odontogenic cyst that develops between the upper lip and nasal vestibule. It has unsure pathogenesis. It has a history of slow-growing lesions, and clinically on palpation gives a floating touch. Usually, there is an elevation of the upper lip. The swelling usually, in most cases, is asymptomatic produces a localised swelling along with varying degrees of nasal obstruction. We present a case of a nasolabial cyst which was clinically diagnosed as a lipoma because of its unusual location in the upper lip in a 46-year-old man, which slowly increased in size over a period of 6 months with the association of slight pain on palpation and facial disfigurement. Our objective is to alert the dental professionals about the unusual presentation of nasolabial cyst in the upper lip, which may become a hurdle in clinical diagnosis.